Concomitant colonic disease (Montreal L3) and re‐resectional surgery are predictors of clinical recurrence following ileocolonic resection for Crohn's disease. (November 2015) - Morar, P. S.; Faiz, O.; Hodgkinson, J. D.; Zafar, N.; Koysombat, K.; Purcell, M.; Hart, A.; Warusavitarne, J.
Abstract Aim Ileocolonic resection is reserved for patients with moderate to severe Crohn's disease. Postoperative clinical recurrence can occur in up to 55% of patients within 5 years. Predicting the risk of recurrence is key in deciding upon appropriate treatment strategies. This study aims to determine the incidence of postoperative clinical recurrence and predictors of recurrence in a specialist institution. Method The clinical case records of 142 patients who underwent either a one‐stage or two‐stage procedure for ileocolonic Crohn's disease from 1 January 2005 to 31 December 2010 were reviewed. Preoperative, perioperative and postoperative variables were extracted. Postoperative clinical recurrence was defined as an initiation or change in medical treatment for recurrent symptoms with endoscopic or radiological evidence of active disease. Time to clinical recurrence was measured in months after surgery. Univariate and multivariate analyses were performed. Results Over the 6‐year period, follow‐up data were obtained on 142 patients over a median of 28.5 months. Clinical recurrence was demonstrated in 59 (41.5%) patients. The proportion of patients with clinical recurrence at 5 years was 48.2%. Predictors of recurrence included a re‐resection for recurrent disease [hazard ratio (HR) 1.9; 95% CI 1.1–3.3; P = 0.02] and ileocolonic disease (HR 1.7; 95% CI 1.0–2.9; P = 0.05). Conclusion Identifying the predictors for postoperative clinical recurrence is important for determining the postoperative strategy. This study provides a unique perspective on the incidence of recurrence and associated predictors from the perspective of a specialist unit.